Quality and Safety Challenges in Inpatient Pediatric Care during the COVID‐19 Pandemic: A National Qualitative Study. (15th September 2021) - De Angulo, Nadia Roessler; Penwill, Nicole; Pathak, Priya; Elster, Martha; Ja, Clairissa; Hochreiter, Daniela; Wilson, Karen; Newton, Jacqueline; Kaiser, Sunitha
Abstract : Research Objective: The COVID‐19 pandemic has necessitated rapid changes in healthcare delivery, including surge planning and modifying healthcare delivery environments and practices. Our objective was to identify the major resulting challenges for quality and safety of pediatric inpatient care. Study Design: We conducted semi‐structured video interviews. Using constant comparative methods, we iteratively coded data to identify themes related to pediatric inpatient quality and safety challenges during the pandemic. Population Studied: We purposefully sampled from community and children's hospitals serving pediatric patients in the 6 U.S. states with the highest COVID‐19 hospitalization rates at the onset of the pandemic (NY, NJ, DC, MA, CT, LA). We recruited 2 front‐line clinicians per site (mix of administrators, nurses, physicians). Principal Findings: Twenty‐four participants from 12 hospitals were interviewed. The most commonly encountered themes are detailed in Table 1. Changes in healthcare delivery practices potentially impacting quality and safety of inpatient pediatric care included: 1) limits on family and caregiver visitation, which may have hindered gathering important details for diagnosis and engaging in shared‐decision making about management; 2) personal protective equipment and isolation practices, which may have compromised effective communication with caregivers and interpreters; 3) changes in quality improvement (QI) infrastructure and activities, with potential decreases in monitoring and safety efforts; 4) difficulties defining and providing high‐quality care for children with COVID‐19 and multi‐system inflammatory syndrome in children, both novel diagnoses; and 5) potential increases in safety events due to decreased direct contact with patients and monitoring (e.g., wound infections, central line‐associated bloodstream infections and catheter‐associated urinary tract infections). Table 1 : Theme Exemplary Quote Limiting family or caregiver visitation "In challenging diagnoses, even if it wasn't COVID‐related, you couldn't have both parents there at the same time." Experiencing personal protective equipment or isolation status as a barrier to communication "With non‐English speaking parents, we were trying to use an interpreter phone with an N9, an extra mask, the negative pressure circulator running in the background. Trying to get a good history and to provide quality care was really brutal." Difficulty maintaining high‐quality care "These people would not have any care. They would be sitting in the ED in the hallway, one ED doc taking care of 50 patients. No, you were not qualified to take care of this patient, but this is a pandemic." Changes in QI operations (staffing, data monitoring, QI activities) "Everything non‐essential stopped. Meetings canceled, research on hold, IRB halted, labs shut down. We have mandatory reporting on things like sepsis. There was too much else going on, we stopped measuring certain things." Increasing healthcare‐associated safety events or harms "We had an uptake in our CLABSI, in every healthcare‐associated condition we were capable of tracking. After the fact, because that was not the priority." Conclusions: This national qualitative study of early COVID‐19 epicenters described changes in several domains of healthcare delivery affecting quality and safety of pediatric inpatient care. Implications for Policy or Practice: The several potential areas of focus identified can help clinicians and hospital leaders plan for safe and high‐quality care for hospitalized children, during this ongoing crisis and for future pandemics. Primary Funding Source: Agency for Healthcare Research and Quality.